2008
DOI: 10.1002/jmv.21311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a variant virus that caused de novo hepatitis B without elevation of hepatitis B surface antigen after chemotherapy with rituximab

Abstract: Hepatitis B virus (HBV) reactivation in hepatitis B surface antigen (HBsAg)-negative patients following treatment with rituximab has been reported increasingly. The aim of this study was to investigate the molecular mechanisms underlying HBV reactivation in an HBsAg-negative patient. HBV was reactivated in a 75-year-old man following chemotherapy with rituximab, without elevation of HBsAg. The patient's full-length HBV genome was cloned and the entire sequence was determined. Transfection studies were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Similar reports exist with combined rituximab chemotherapy, suggesting that adding steroids or fludarabine to rituximab may result in a high frequency of drug resistance [49] . We believe that the relationship of immunosuppression and HBV genomic mutations requires further study because it remains undetermined whether long-term preventive lamivudine treatment combined with strong immunosuppression treatment is possible.…”
Section: Risk Factors For Hbv Reactivationsupporting
confidence: 68%
“…Similar reports exist with combined rituximab chemotherapy, suggesting that adding steroids or fludarabine to rituximab may result in a high frequency of drug resistance [49] . We believe that the relationship of immunosuppression and HBV genomic mutations requires further study because it remains undetermined whether long-term preventive lamivudine treatment combined with strong immunosuppression treatment is possible.…”
Section: Risk Factors For Hbv Reactivationsupporting
confidence: 68%
“…The patient had been anti-HBc-and anti-HBs-positive before therapy and had obviously harbored the occult variant in the liver. A similar case with heavily mutated HBsAg was published recently by Miyagawa et al [28] .…”
Section: Reactivation Of Obi Under Immunosuppressionmentioning
confidence: 64%
“…It can be fatal, however, after immune reconstitution. To make things worse, it is often caused by escape mutants [26][27][28] . Table 2 lists 9 cases which we have analyzed [W.H.G., unpubl.].…”
Section: Reactivation Of Obi Under Immunosuppressionmentioning
confidence: 99%
“…However, almost all previously reported cases of HBV reactivation after rituximab therapy have had negative anti-HBs at the time of the HBV flares [1,20], with the exception of one case report [21]. In that case, Miyagawa et al reported that one patient with persistent antiHBs had hepatitis caused by a mutated HBV strain that did not produce HBsAg [21]. In our study, no patient with initial antiHBs titers greater than 100 mIU/mL lost anti-HBs, suggesting low risk of HBV reactivation after rituximab therapy.…”
Section: Discussionmentioning
confidence: 92%